Integrating Traditional Games into Teacher Training Programs in Pinrang Regency to Enhance School Readiness and Child Development - Sitti Nurhidayah Ilyas (Universitas Muhammadiyah Enrekang, 2024)
This study aimed to analyze the integration of traditional games into teacher training programs as a strategy to enhance school readiness and holistic child development in Pinrang Regency, focusing on early-grade primary school teachers and kindergarten teachers. The research employed a mixed-methods design with a quasi-experimental approach, involving teachers, children, and parents from rural and urban areas. Teacher training sessions introduced culturally responsive, play-based strategies by integrating relevant traditional games. Children's developmental domains, including cognitive, motor, social-emotional, and linguistic, were assessed before and after the intervention. The results revealed significant improvements across all measured domains. Children exhibited better problem-solving abilities, enhanced cooperation, improved language skills, and better motor coordination. Teachers gained confidence in implementing intentional play-based teaching methods, while parents became more engaged in their children's educational experiences. Contextual differences between rural and urban areas underscored the adaptability of this approach to diverse environments. Cultural responsiveness emerged as a critical factor in fostering inclusivity and meaningful learning engagement. This study demonstrates that integrating traditional games into teacher training can positively impact school readiness. Culturally responsive, play-based methodologies enrich educational experiences and serve as a guide for future research, policy development, and educational practice.